A low-power, radiation-resistant, Silicon-Drift-Detector array for extraterrestrial element mapping - Ramsey, B D; Gaskin, J A; Elsner, R F; Chen, W; Carini, G A; Geronimo, G De; Keister, J; Li, S; Li, Z; Siddons, D P; Smith, G (Journal of instrumentation, 2012)
We are developing a modular Silicon Drift Detector (SDD) X-Ray Spectrometer (XRS) for measuring the abundances of light surface elements (C to Fe) fluoresced by ambient radiation on remote airless bodies. The value of fluorescence spectrometry for surface element mapping is demonstrated by its inclusion on three recent lunar missions and by exciting new data that have recently been announced from the Messenger Mission to Mercury. The SDD-XRS instrument that we have been developing offers excellent energy resolution and an order of magnitude lower power requirement than conventional CCDs, making much higher sensitivities possible with modest spacecraft resources. In addition, it is significantly more radiation resistant than x-ray CCDs and therefore will not be subject to the degradation that befell recent lunar instruments. In fact, the intrinsic radiation resistance of the SDD makes it applicable even to the harsh environment of the Jovian system where it can be used to map the light surface elements of Europa. In this paper, we first discuss our element-mapping science-measurement goals. We then derive the necessary instrument requirements to meet these goals and discuss our current instrument development status with respect to these requirements.